Meningkatkan Hasil Belajar Sosiologi Melalui Kardi Pinter - Hanna Ari Tri Noeryanti (Teknodika, 2020)
The pupose of this action research is help students to achive higher score and develop their character and ability to adapt and solve the problems. Kardi Pinter stands for cards, discussion and guided inqury. The teacher explain the material so that students can guess the material explained by teacher to have a correct understanding in terms that are introduced. Project assigment begin by looking at enviromental potential and create new innovations. Student projects assigments to obtain an analysis enhanced through joint project in a group by using RRA method : transect, social mapping, problem three analysis, foccused group discussion. Kardi Pinter learning outcomes generate enthusiasm in caring for environment and learning achievement significantly.Kardi Pinter has been able to improved students achievement to have complrtion value by 65%.There fore replication of Kardi Pinter model learning is feasible to be done as a solution to improve student learning with the same conditions as class XII C.